2020
DOI: 10.1002/ijc.32920
|View full text |Cite
|
Sign up to set email alerts
|

Colibactin‐positive Escherichia coli induce a procarcinogenic immune environment leading to immunotherapy resistance in colorectal cancer

Abstract: Colibactin‐producing E. coli (CoPEC) are frequently detected in colorectal cancer (CRC) and exhibit procarcinogenic properties. Because increasing evidence show the role of immune environment and especially of antitumor T‐cells in CRC development, we investigated the impact of CoPEC on these cells in human CRC and in the APCMin/+ mice colon. T‐cell density was evaluated by immunohistochemistry in human tumors known for their CoPEC status. APCmin/+ mice were chronically infected with a CoPEC strain (11G5). Immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 47 publications
1
68
0
Order By: Relevance
“…Decreased tumor-infiltrating lymphocytes (TILs) in the invasive CRC margin is associated with pks + E. coli ( 101 ). Moreover, APC Min/+ mice exposed to colibactin-producing E. coli exhibit more polyps and decreased CD3 + CD8 + T-cells than noninfected animals or infected with pks- lacking E. coli strains, suggesting colibactin induces a carcinogenic microenvironment ( 101 ).…”
Section: Gut Microbiomementioning
confidence: 99%
“…Decreased tumor-infiltrating lymphocytes (TILs) in the invasive CRC margin is associated with pks + E. coli ( 101 ). Moreover, APC Min/+ mice exposed to colibactin-producing E. coli exhibit more polyps and decreased CD3 + CD8 + T-cells than noninfected animals or infected with pks- lacking E. coli strains, suggesting colibactin induces a carcinogenic microenvironment ( 101 ).…”
Section: Gut Microbiomementioning
confidence: 99%
“…While colibactin can directly promote oncogenic transformation by DNA alkylation and subsequent mutagenesis in epithelial cells [ 6 , 9 , 23 , 29 ], its role in CRC progression extends beyond these activities by helping to establish a pro-carcinogenic environment supporting tumor growth [ 62 , 63 , 64 ]. After pks -induced DNA damage, cells may undergo apoptosis, transformation, or senescence.…”
Section: Colibactin Activity In Physiologic Contextmentioning
confidence: 99%
“…These changes may occur near cells that have acquired pks -generated mutations in the APC or p53 pathways after colibactin exposure [ 29 ], further promoting unrestricted growth and tumor proliferation. A recent study demonstrated that the pks + E. coli strain 11G5 translocates to mesenteric lymph nodes in Apc Min/+ mice, with a concomitant reduction of some cytotoxic T cell lineages and an increase in regulatory T cells within infected lymph nodes [ 64 ]. Furthermore, levels of cytotoxic T cells are reduced within the colonic mucosa of 11G5-colonized mice and invasive margins from tumor biopsies from CRC patients colonized by pks + E. coli [ 64 ], suggesting that colibactin-producing microbes may create a pro-carcinogenic environment within the gut by modulating immune cell activity.…”
Section: Colibactin Activity In Physiologic Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…The colonization of CRC patients by CoPEC is associated with a decrease of tumor-infiltrating T lymphocytes (CD3+ T-cells). Similarly, in mice, CoPEC chronic infection decreases CD3+ and CD8+ T-cells and increases colonic inflammation, suggesting that pks+ E. coli could promote a pro-carcinogenic immune environment through impairment of antitumor T-cell response [ 74 ]. Moreover, colitis-susceptible IL-10-deficient mice showed increased formation of invasive carcinoma when colonized with CoPEC, whereas deletion of the pks genotoxic island from these E. coli strains decreased tumor multiplicity and invasion [ 72 , 75 ].…”
Section: Bacterial Protein Toxins Causing Genome Instabilitymentioning
confidence: 99%